(untitled) (Journal of Political Issues, 2020)
In the pesantren tradition the pattern of interaction between the kyai and the santri is very sacred. Culture of obedience and reverence in the pesantren environment is automatically attached to every santri. For students, this obedience is an honor to get blessings from the ulema. This paper aims to explore the paradigm shift of santri in determining political choices in the electoral process. This research is a descriptive study with qualitative methods. Determination of informants using techniques purposive to adjust data needs for research purposes. The results showed a paradigm shift that used to be very dependent on wasilah, now is more open in person. Santri’s knowledge of good political science and concern about politics are the main factors in being able to formulate personal political choices without any intervention from the pesantren.